Adherence and out‐of‐pocket costs among Medicare beneficiaries who are prescribed oral targeted therapies for advanced prostate cancer. Issue 23 (14th September 2020) - Caram, Megan E. V.; Oerline, Mary K.; Dusetzina, Stacie; Herrel, Lindsey A.; Modi, Parth K.; Kaufman, Samuel R.; Skolarus, Ted A.; Hollenbeck, Brent K.; Shahinian, Vahakn
Abstract : Background: Abiraterone and enzalutamide are high‐cost oral therapies that increasingly are used to treat patients with advanced prostate cancer; these agents carry the potential for significant financial consequences to patients. In the current study, the authors investigated coping and material measures of the financial hardship of these therapies among patients with Medicare Part D coverage. Methods: The authors performed a retrospective cohort study on a 20% sample of Medicare Part D enrollees who underwent treatment with abiraterone or enzalutamide between July 2013 and June 2015. The authors described the variability in adherence rates and out‐of‐pocket payments among hospital referral regions in the first 6 months of therapy and determined whether adherence and out‐of‐pocket payments were associated with patient factors and the socioeconomic characteristics of where a patient was treated. Results: There were 4153 patients who filled abiraterone or enzalutamide prescriptions through Medicare Part D in 228 hospital referral regions. The mean adherence rate was 75%. The median monthly out‐of‐pocket payment for abiraterone and enzalutamide was $706 (range, $0‐$3505). After multilevel, multivariable adjustment for patient and regional factors, adherence was found to be lower in patients who were older (69% for patients aged ≥85 years vs 76% for patients aged <70 years; P  < .01) and in those with low‐income subsidies (69% in those with a subsidy vs 76% in those without a subsidy; P  < .01). Both Hispanic ethnicity and living in a hospital referral region with a higher percentage of Hispanic beneficiaries were found to be independently associated with higher out‐of‐pocket payments for abiraterone and enzalutamide. Conclusions: There were substantial variations in the adherence rate and out‐of‐pocket payments among Medicare Part D beneficiaries who were prescribed abiraterone and enzalutamide. Sociodemographic patient and regional factors were found to be associated with both adherence and out‐of‐pocket payments. Abstract : Measures of financial hardship appear to vary substantially among patients who fill prescriptions for abiraterone or enzalutamide through Medicare Part D. Socioeconomic factors at the patient and regional level are associated with financial hardship measures.